Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can you prove that if each element of group is inverse to itself then the group is commutative?

share|cite|improve this question
This has to be a duplicate! I have searched though, but to no avail. The closest I could find was this question. – user1729 Oct 26 '12 at 8:58
Plenty of answers, but I'm the only one who's up-voted the question so far. – Michael Hardy Jun 9 '14 at 19:02
up vote 3 down vote accepted

HINT: If $a,b\in G$, then $(ab)^2=1_G=a^2b^2$.

share|cite|improve this answer

Let $g \in G$; we know that $g = g^{-1}$, and that $g^{-1} \in G$ because groups contain the inverse of each of their elements. Now suppose $x,y \in G$. Then $xy \in G$ by closure under products, and so $xy = (xy)^{-1} = y^{-1}x^{-1} = yx$, where we used the fact the $x=x^{-1}$ and $y = y^{-1}$ in the last step. This shows that $G$ is a commutative group.

share|cite|improve this answer
IMHO, the most elegant answer. – beroal Mar 24 '15 at 12:08

The group being commutative means that $ \forall a, b \in G$, $ab = ba$. Since G is a group, $ab \in G$ and so is it's own inverse, which means $(ab)(ab) = 1$ multiplying on the left by a and then by b gives $bab = a$ and then $ab = ba$ as required.

share|cite|improve this answer

Since you've got it, $$xy = \overline {xy} = \overline y \overline x = yx$$

share|cite|improve this answer
Please consider using $\LaTeX$ to format your answers. – Ali Caglayan Oct 22 '14 at 8:59
@Alizter Thank you for the reference: I didn't know how. – Thumbnail Oct 22 '14 at 9:20

Since the problem is quite elementary, I'll give you a hint:

being one's own inverse means that $a^2=1$ for all $a$, what do you know about the identity of a group?

share|cite|improve this answer

say a and b belong to G a=(a)^-1 and b=(b)^-1

=> (axb) = ((a^-1) x (b^-1))

=> axb = (bxa)^-1 -------------------------------(1)

let c=bxa

it is obvious from closure prop. that c belongs to G so c=(c)^-1 or (bxa)=(bxa)^-1 ---------------------(2)

from (1) and (2) axb=bxa Hence it is a commutative group

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.